2003
DOI: 10.1037/0882-7974.18.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Looking back and looking ahead: Adult age differences in consistency of diachronous ratings of subjective well-being.

Abstract: The goal of this study is to investigate the consistency of diachronous ratings of subjective well-being (SWB). A heterogeneous sample (25-74-year-olds; N ϭ 3,596) provided ratings of their present SWB, reconstructed their SWB of 10 years ago, and anticipated their SWB 10 years from now. Developmental tasks and self-evaluative principles were used to predict age differences in diachronous consistency. As predicted, in young adulthood, past SWB was rated lower and future SWB higher than present SWB. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
93
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 54 publications
17
93
1
4
Order By: Relevance
“…While for older adults, with decreasing resources, it seems adaptive to conceive of the future as being close to the present and the past and perceiving them as belonging to one category (assimilation effect; Schwarz & Strack, 1999). In this vein, a recent study found that in old age perceptions of ourselves in the past and the future have a stronger predictive value for our well-being in the present than in young and middle adulthood, which may in fact contribute to perceiving fewer changes (Staudinger, Bluck, & Herzberg, 2003).…”
Section: Self-evaluation: Lifetime Comparisonsmentioning
confidence: 99%
“…While for older adults, with decreasing resources, it seems adaptive to conceive of the future as being close to the present and the past and perceiving them as belonging to one category (assimilation effect; Schwarz & Strack, 1999). In this vein, a recent study found that in old age perceptions of ourselves in the past and the future have a stronger predictive value for our well-being in the present than in young and middle adulthood, which may in fact contribute to perceiving fewer changes (Staudinger, Bluck, & Herzberg, 2003).…”
Section: Self-evaluation: Lifetime Comparisonsmentioning
confidence: 99%
“…Interestingly, the discrepancy between actual and ideal development seems to decrease with age (Ryff, 1991;Staudinger, Bluck, & Herzberg, 2003). Self-ideal similarities as well as favorable comparisons of oneself to most other people (Heckhausen & Krueger, 1993) are both hypothesized to contribute to subjective well-being in older ages.…”
Section: Well-beingmentioning
confidence: 99%
“…Using this scale, Shmotkin (1991a) found a consistent configuration whereby progressive age (in a cross-sectional design) was associated with stability in ratings for the present, a decline for the future, and an increase for the past. Other extensions of measures into past and future evaluations (Fleeson & Heckhausen, 1997;Pavot, Diener, & Suh, 1998;Ryff, 1991;Staudinger, Bluck, & Herzberg, 2003) also demonstrate the dynamics of temporal perspectives. In fact, time-referent ratings of SWB contain a narrative about a person's progression in time: They tell a story.…”
Section: Ingredients Of Narrative Swbmentioning
confidence: 99%